A Tree: Planted and Growing - Christina A. Christie (Journal of MultiDisciplinary Evaluation)
Background: Evaluation theory classification systems have been developed since the field’s early stages of theory development. Many have been published with the goal of promoting further understanding of the ways in which theoretical ideas relate both philosophically and in practice. This intends to promote a better understanding of the development and evolution of one of the classification systems, the Evaluation Theory, developed by Alkin and Christie first in the late 1990s and is in its most recent version, published in 2023.